Placental imprinted gene expression mediates the effects of maternal psychosocial stress during pregnancy on fetal growth. (10th April 2019) - Lambertini, L.; Li, Q.; Ma, Y.; Zhang, W.; Hao, K.; Marsit, C.; Chen, J.; Nomura, Y.
Abstract: Imprinted genes uniquely drive and support fetoplacental growth by controlling the allocation of maternal resources to the fetus and affecting the newborn's growth. We previously showed that alterations of the placental imprinted gene expression are associated with suboptimal perinatal growth and respond to environmental stimuli including socio-economic determinants. At the same time, maternal psychosocial stress during pregnancy (MPSP) has been shown to affect fetal growth. Here, we set out to test the hypothesis that placental imprinted gene expression mediates the effects of MPSP on fetal growth in a well-characterized birth cohort, the Stress in Pregnancy (SIP) Study. We observed that mothers experiencing high MPSP deliver infants with lower birthweight ( P =0.047). Among the 109 imprinted genes tested, we detected panels of placental imprinted gene expression of 23 imprinted genes associated with MPSP and 26 with birthweight. Among these genes, five imprinted genes ( CPXM2, glucosidase alpha acid ( GAA), GPR1, SH3 and multiple ankyrin repeat domains 2 ( SHANK2) and THSD7A ) were common to the two panels. In multivariate analyses, controlling for maternal age and education and gestational age at birth and infant gender, two genes, GAA and SHANK2, each showed a 22% mediation of MPSP on fetal growth. These data provide new insights into the role that imprinted genes play in translating the maternal stress message into a fetoplacental growth pattern.